COMMUNICATION AS A FACTOR IN THE SUCCESS OF DOWNSIZING - Josefa Melgar Bayardo; Fernando Matías Reche; Marie Leiner De La Cabada (European Scientific Journal, ESJ, 2013)
In recent years a large number of organizations, both public and private, have implemented downsizing, with the aim of improving productivity, efficiency and competitiveness. But studies show that the results are not always as expected, with firms reporting negative effects among their workers in terms of stress, uncertainty, insecurity and fear of losing their jobs. The current work investigates the relation between internal communication, job satisfaction and organizational commitment in firms implementing this change strategy. Results show that internal communication has a positive effect on job satisfaction, and that job satisfaction, in turn, has a positive effect on organizational commitment.